Pelanggaran Pembatasan Kewenangan Aparat Penegak Hukum Dalam Hukum Acara Pidana Terkait Kasus Kekerasan Dalam Penyidikan - Annisa Febyanti; Bilqisti Kurrotul Aini; Andi Laila Qadrianti Putri; Berliana Putri Wiraka; Muhammad Althaf Faishal; Nurul Amaliyah Putri (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The police apparatus is one of the law enforcement officers as a state instrument that plays a role in maintaining public security and order, as well as providing protection, protection and services to the community. However, the facts in the field say, there are still many violations of the principles of the rule of law in the realm of criminal procedure law, one of which is violence committed by law enforcement officials in the realm of investigation. The purpose of this writing is to find out how legal protection is given to victims of violence in investigations and to find out how the role of law enforcement officials should be in interpreting authority and power. The research method used by the author is normative legal research using data collection techniques through document study activities on secondary data. The results obtained from this writing are that suspects who experience violence in the investigation can make legal efforts through their family or legal counsel in accordance with what is regulated in Article 77 of the Criminal Procedure Code. In addition, in the context of accountability, law enforcement officials must be prepared to account for their actions and decisions to interested parties, including the community at large.